2019
DOI: 10.1186/s12915-019-0680-2
|View full text |Cite
|
Sign up to set email alerts
|

Ancient role of vasopressin/oxytocin-type neuropeptides as regulators of feeding revealed in an echinoderm

Abstract: Background: Vasopressin/oxytocin (VP/OT)-type neuropeptides are well known for their roles as regulators of diuresis, reproductive physiology and social behaviour. However, our knowledge of their functions is largely based on findings from studies on vertebrates and selected protostomian invertebrates. Little is known about the roles of VP/OT-type neuropeptides in deuterostomian invertebrates, which are more closely related to vertebrates than protostomes. Results: Here, we have identified and functionally cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 77 publications
(112 reference statements)
5
78
0
Order By: Relevance
“…Therefore, here, we investigated the effect of in vivo injection of ArSS2 in A. rubens and found that it causes partial eversion of the cardiac stomach. Our previous studies have revealed that both S2 and asterotocin also cause cardiac stomach eversion in A. rubens but, consistent with their relative efficacy as cardiac stomach relaxants in vitro, asterotocin is much more effective and potent than S2 in triggering cardiac stomach eversion [67]. Accordingly, here, we found that asterotocin is much more effective than ArSS2 in triggering cardiac stomach eversion, consistent with their relative effectiveness as cardiac stomach relaxants in vitro.…”
Section: Functional Characterization Of Arss2 In the Starfishsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, here, we investigated the effect of in vivo injection of ArSS2 in A. rubens and found that it causes partial eversion of the cardiac stomach. Our previous studies have revealed that both S2 and asterotocin also cause cardiac stomach eversion in A. rubens but, consistent with their relative efficacy as cardiac stomach relaxants in vitro, asterotocin is much more effective and potent than S2 in triggering cardiac stomach eversion [67]. Accordingly, here, we found that asterotocin is much more effective than ArSS2 in triggering cardiac stomach eversion, consistent with their relative effectiveness as cardiac stomach relaxants in vitro.…”
Section: Functional Characterization Of Arss2 In the Starfishsupporting
confidence: 87%
“…At 10 −6 M, there was no significant difference in the efficacy of ArSS2 and S2, but the efficacy of these peptides was approximately 50% of that of asterotocin ( figure 11). A previous study revealed that asterotocin is much more effective as a cardiac stomach relaxant than S2 [67] and here, we show that asterotocin is more effective than both S2 and ArSS2 as a cardiac stomach relaxant when tested at 10 −7 or 10 −6 M.…”
Section: Functional Characterization Of Arss2 In the Starfishsupporting
confidence: 73%
“…Moreover, the effect of asterotocin on body posture was so powerful that it adversely affected the ability of starfish to right themselves when upturned. Collectively, the findings of this study indicate that asterotocin signaling has an important physiological/behavioral role in triggering the unusual extra-oral feeding behavior of the starfish A. rubens (131). Expression of the asterotocin precursor has also been investigated in the free-swimming larvae of A. rubens, with transcripts detected during the brachiolaria larval stage in cells located at the tips of the brachia and associated with the adhesive disk-structures that mediate larval attachment to the substratum prior to metamorphosis (132).…”
Section: Echinodermatamentioning
confidence: 58%
“…Sequencing of the neural transcriptome of the starfish A. rubens enabled identification of a transcript encoding a VP/OT-type precursor protein comprising the neuropeptide "asterotocin" (130) and the structure of this peptide (CLVQDCPEG-NH 2 ) has been confirmed using mass spectrometry (131). An unusual characteristic of asterotocin is that it has acidic residues at positions 5 and 8, which are usually occupied by a basic or hydrophobic residue in other VP/OT-type peptides ( Table 1).…”
Section: Echinodermatamentioning
confidence: 99%
See 1 more Smart Citation